2021
DOI: 10.1002/rth2.12484
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of pulmonary embolism: A mixed‐methods study

Abstract: Background Patients diagnosed with pulmonary embolism (PE) are reported to experience symptoms of posttraumatic stress disorder (PTSD) and existential anxiety following their diagnosis. They may also experience negative changes in perspective and hypervigilance of PE symptoms. Objective The aim of this study was to document the mental and emotional experience associated with PE diagnosis through the lens of PTSD, to better understand the factors involved in psychological distress following receipt of a PE diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 23 publications
3
39
0
Order By: Relevance
“…Other studies have shown that lack of adequate understanding may drive patients to seek information from potentially dubious sources. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that lack of adequate understanding may drive patients to seek information from potentially dubious sources. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Complications such as chronic thromboembolic pulmonary hypertension, postthrombotic syndrome, and bleeding are well characterized in the thrombosis literature, and much research has focused on optimizing therapy to mitigate these adverse outcomes. However, patients who have experienced pulmonary embolism or deep vein thrombosis consistently report other mental health complications such as anxiety, depression, and posttraumatic stress disorder 1‐3 . In fact, when patients with VTE are interviewed about their lived experience, they are seldom preoccupied by their physical recovery and instead focus on psychological distress, worry, and well‐being.…”
Section: Figurementioning
confidence: 99%
“…However, patients who have experienced pulmonary embolism or deep vein thrombosis consistently report other mental health complications such as anxiety, depression, and posttraumatic stress disorder. 1 , 2 , 3 In fact, when patients with VTE are interviewed about their lived experience, they are seldom preoccupied by their physical recovery and instead focus on psychological distress, worry, and well‐being.…”
mentioning
confidence: 99%
See 2 more Smart Citations